Metallurgical Design and Industry Prehistory to the Space Age (Springer International Publishing, 2018)
This edited volume examines metallurgical technologies and their place in society throughout the centuries. The authors discuss metal alloys and the use of raw mineral resources as well as fabrication of engineered alloys for a variety of applications. The applications covered in depth include financial, mining and smelting, bridges, armor, aircraft, and power generation. The authors detail the multiple levels and scales of impact that metallurgical advances have had and continue to have on society. They include case studies with guidance for future research design and innovation of metallic materials relevant to societal needs. Includes case studies written by industry professionals with guidance for future research design and innovation; Demonstrates metal materials design that reflects relevant societal needs; Covers a broad range of applied materials used in aircraft, armor, bridges, and power generation, among others.